PROGRESS IN THE USE OF INNOVATION IN RISK MANAGEMENT. CASE STUDY ON NATURAL GAS AND SERVICE SECTORS IN BULGARIA - P. Biolcheva; S. Ivanov; V. Bozev (Trakia Journal of Sciences)
In recent years, companies are facing more and more types of risks with different levels of complexity. Inevitably this reflects also on the way how the risk is identified, evaluated and managed. One of the innovative risk management solutions is the use of artificial intelligence (AI). Artificial intelligence will create a foundation for more resilient, sustainable, adaptive, and well-prepared companies which could face environmental changes without being impacted so heavily. The purpose of the study described in this paper is to conduct empirical research to examine the progress of intelligent risk management implementation and the attitude towards it in companies from two sectors of the Bulgarian economy – services and gas. The two sectors will be compared and it will be statistically validated if there is a difference in how the companies from the gas and services sectors see the artificial intelligence and its benefits. Based on the results, at the end, a proposal for improved and innovative risk management will be made. The results of the survey and the empirical study will show what will be the future direction of the research in the field of artificial intelligence and its implementation in risk management.